2014
DOI: 10.1021/ar5003158
|View full text |Cite
|
Sign up to set email alerts
|

Keep on Moving: Discovering and Perturbing the Conformational Dynamics of Enzymes

Abstract: ConspectusBecause living organisms are in constant motion, the word “dynamics” can hold many meanings to biologists. Here we focus specifically on the conformational changes that occur in proteins and how studying these protein dynamics may provide insights into enzymatic catalysis.Advances in integrating techniques such as X-ray crystallography, nuclear magnetic resonance, and electron cryomicroscopy (cryo EM) allow us to model the dominant structures and exchange rates for many proteins and protein complexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 75 publications
2
91
0
Order By: Relevance
“…The results are consistent with a catalytic mechanism sufficiently described by conformational and electrostatic fluctuations on slower time scales. 36,45,46 The ecDHFR protein creates a geometric and electrostatic catalytic cage where the reaction coordinate is formed by favorable electrostatic apposition of the reactants.…”
Section: Resultsmentioning
confidence: 99%
“…The results are consistent with a catalytic mechanism sufficiently described by conformational and electrostatic fluctuations on slower time scales. 36,45,46 The ecDHFR protein creates a geometric and electrostatic catalytic cage where the reaction coordinate is formed by favorable electrostatic apposition of the reactants.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic cycle of Escherichia coli DHFR (EcDHFR) consists of at least five sub-states corresponding to intermediates associated with the substrate (DHF) and cofactor (NADPH) binding, the chemical step of hydride transfer and the product (THF) and spent cofactor (NADP + ) release. Using 15 N spin-relaxation NMR techniques (mostly the rcCPMG described above), Wright and co-workers discovered that at each intermediate along the catalytic cycle represents sampling of populations from multiple conformational sub-states (Figure 7) (Bhabha, Biel, & Fraser, 2015; Boehr, Dyson, et al, 2006; Boehr, McElheny, et al, 2006). …”
Section: Examples Of Conformational Sub-states In Enzyme Catalysismentioning
confidence: 99%
“…They showed that free energies of a few kcal/mol can be derived from only a slight stiffening of a few of the many global dynamic modes of motion available to a protein. With the increasing understanding of the importance of dynamics in enzyme catalysis (see the recent virtual special issue of Accounts of Chemical Research on 'Protein Motions in Catalysis'; Bhabha et al 2015;Callender and Dyer 2015;Hanoian et al 2015;Klinman 2015;Kohen 2015;Palmer 2015) and in protein function in general, the importance of dynamics as a contributory mechanism in allosteric effects is now recognised (Jardetzky 1996;Kern and Zuiderweg 2003;Tsai et al 2008).…”
mentioning
confidence: 99%